Depression and suicidal ideation among individuals with type-2 diabetes mellitus, a cross-sectional study from an urban slum area of Karachi, Pakistan - Sharif, Hina; Jan, Shah Sumaya; Sharif, Sana; Seemi, Tooba; Naeem, Hira; Jawed, Zahida (Frontiers in Public Health, 2023)
Background: Suicidal thoughts and depression are associated with Diabetes patients, especially patients with low socioeconomic backgrounds and prolonged illness. Objective: We aimed to estimate the suicidal thoughts and depression among type 2 Diabetes (T2 D) patients in the slums of Karachi. Methods: This cross-sectional study was conducted across 38 locations in the slums of Karachi to understand depression, suicidal thoughts, and other supporting factors of depression associated with T2D. The Oslo 3-item social support scale, the patient health questionnaire-9 (PHQ-9) scale, and the Ask Suicide Screening Questions were used to screen the patients. Results: A total of 504 study participants were interviewed, with a response rate of 98%. The prevalence of depression among diabetic patients was 30.83%, and suicidal ideation was 20.39%. In the final multivariate analysis, being socioeconomically poor, physically disabled, and having poor social support were independent predictors of depression. Conclusion: Diabetes, low socioeconomic level, a lack of social support, and physical disability were all linked to depression. Therefore, trained health providers should conduct an early depression-focused routine screening for diabetes patients.